Ultrasonic assisted exfoliation for efficient production of RuO2 monolayer nanosheets. Issue 20 (25th August 2021) - Kim, Se Yun; Kim, Sang-il; Kim, Mun Kyoung; Kim, Jinhong; Mizusaki, Soichiro; Ko, Dong-Su; Jung, Changhoon; Yun, Dong-Jin; Roh, Jong Wook; Kim, Hyun-Sik; Sohn, Hiesang; Lim, Jong-Hyeong; et al.
Abstract : RuO2 monolayer nanosheets can be easily synthesized by an ultrasonic assisted exfoliation process. Abstract : Two-dimensional (2D) metal oxide nanosheets have been synthesized through ion exchange reactions. However, they require a long time and lead to low production yields due to the molecular size of the intercalant and reaction activation energies. To reduce the processing time and accelerate the production yield, we introduce an ultrasonically supported ion exchange reaction process. We applied ultrasound energy on the solution of RuO2 nanosheets and the intercalant after 3 days of stirring the ion exchange reaction. After 15 min, the yield of RuO2 nanosheets increased by over 50%. In addition, we observed that the lateral size of the RuO2 nanosheets decreased with the applied ultrasonic time. Density functional theory calculations demonstrated that the activation energy of exfoliation is significantly reduced by splitting the RuO2 layers into a small lateral size. This result shows that ultrasound provides energy for 15 min of exfoliation of the RuO2 nanosheets, after which the energy is used to break the RuO2 nanosheets. The experimental and theoretical results suggest that an ultrasonic-supported ion exchange process offers a facile and efficient approach for fabricating 2D metal oxide nanosheets.